PENGARUH PEMBERIAN PUPUK DAUN GANDASIL-D DAN PUPUK ORGANIK CAIR EM4 TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG TANAH (Arachis hipogaea L.) VARIETAS MACAN - Novilda Elizabeth Mustamu (UNIVERSITAS LABUHANBATU, 2019)
This research was conducted in the village of Pare-Pare Hilir, District Marbau, North Labuhanbatu District, North Sumatra province with a height of ± 54 m above sea level for 3 months. The method used was a randomized block design (RAK) factorial combination with 12 treatments and 3 replications, factor Gandasil-D leaf manure consists of 4 levels, namely: D0 = without treatment, D1 = 2 g / liter of water, D2 = 3 grams / liter water, D3 = 4 g / liter of water, while the Liquid Organic Fertilizer EM4 factor consists of 3 levels, namely : E0 = Without treatment, E1 = 10 ml / liter of water, E2 = 12 ml / liter of water. The parameters observed namely plant height (cm), number of leaves (pieces), the number of branches (stalks), number of pods containing cropping (g), the heavy weight of 100 grains seeds (g), the amount of production per plot (g). Treatment provision leaf manure Gandasil-D very significant effect on the parameters number of branches, number of pods per plant contains, and the amount of production per plot, whereas no real influence on the parameters of plant height, leaf number and weight of 100 grains weight of seed. Treatment of Liquid Organic Fertilizer EM4 administration showed a significant influence on the parameters of plant height and number of branches, but there is also a significant effect on the parameters of the number of pods per plant and the amount of production per plot. While there was no significant effect on the parameters of the number of leaves, and the heavy weight of 100 grains of seeds. Interaction between Leaf Fertilizer Gandasil-D and Liquid Organic Fertilizer EM4 did not give the significant effect on all parameters observed. Keywords : Foliar fertilizer Gandasil-D, EM4 liquid organic fertilizer, Arachis hipogaea